High Expression of Interleukin-12A and Its Association with the Clinicopathology and Prognosis of Differentiated Thyroid Cancer. Issue 3 (17th May 2020) - Zhang, Guo-Qiang; Shen, Chen-Tian; Song, Hong-Jun; Qiu, Zhong-Ling; Luo, Quan-Yong
Abstract : Background: The inflammatory microenvironment is closely related to the occurrence and development of cancer. Members of the interleukin-12 (IL-12) cytokine family play synergistic or antagonistic roles in the tumor microenvironment, in the form of classic heterodimers or newly discovered monomers or homodimers. Objective: The purpose of this study was to investigate the association between IL-12A and the clinicopathology and prognosis of differentiated thyroid cancer (DTC). Methods: A total of 101 pathologically confirmed DTC patients were included in this study. Immunohistochemistry was performed to assess IL-12A expression in DTC and corresponding paracancerous tissues. The associations of IL-12A with clinicopathology and prognosis were evaluated. Results: IL-12A was expressed in both normal thyroid tissues and DTC, but its expression level was significantly higher in DTC than in normal thyroid tissues ( p < 0.001). IL-12A was positively correlated with tumor size ( p = 0.027), risk stratification ( p = 0.020), and TNM (Tumor-Node-Metastasis) stage ( p = 0.024), but not with age, sex, pathological type, multifocality, extrathyroid extension, lymph node metastasis, and distant metastasis (all p > 0.05). Lymphocytic thyroiditis was found in 26/101 patients (25.7%), which was negatively associated with IL-12A expression ( p = 0.018). Multivariate logistic regression analysis showed that risk stratification was the significant independent predictor of IL-12A expression. The rate of disease persistence or recurrence (P&R) was 13/101 (12.9%), and a positive relationship was found between IL-12A expression and P&R ( p = 0.020). Disease-free survival was affected by factors such as tumor size, extrathyroid extension, tumor stage (T stage), and IL-12A expression, with p values of 0.006, 0.048, 0.002, and 0.012, respectively. Multivariate Cox proportional-hazards analysis showed that tumor size ≥2 cm (hazard ratio [HR] = 4.041 [95% CI: 1.144–14.274], p = 0.031) and high IL-12A expression (HR = 4.027 [95% CI 1.014–15.994], p = 0.049) were independent predictors of prognosis of DTC patients. Conclusions: IL-12A is highly expressed in DTC and is associated with disease aggressiveness. In addition, IL-12A is an independent predictor of the outcome of DTC.